2011
DOI: 10.1098/rsbl.2011.0807
|View full text |Cite
|
Sign up to set email alerts
|

Male sexual harassment alters female social behaviour towards other females

Abstract: Male harassment of females to gain mating opportunities is a consequence of an evolutionary conflict of interest between the sexes over reproduction and is common among sexually reproducing species. Male Trinidadian guppies Poecilia reticulata spend a large proportion of their time harassing females for copulations and their presence in female social groups has been shown to disrupt female -female social networks and the propensity for females to develop social recognition based on familiarity. In this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…Experimental removal of these 'policing' males dramatically influences play, grooming and aggressive relationships among individuals in the network [22]. Similar 'indirect' effects have been discovered in many organisms including humans [23,24], eusocial insects [25] and guppies [26]; in this context, the term 'indirect' refers to the scenario in which dyadic & 2013 The Author(s) Published by the Royal Society. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental removal of these 'policing' males dramatically influences play, grooming and aggressive relationships among individuals in the network [22]. Similar 'indirect' effects have been discovered in many organisms including humans [23,24], eusocial insects [25] and guppies [26]; in this context, the term 'indirect' refers to the scenario in which dyadic & 2013 The Author(s) Published by the Royal Society. All rights reserved.…”
Section: Introductionmentioning
confidence: 99%
“…everyone except the focal interactants), and analyse the effects of this manipulation on the focal interaction (figure 1). The advantage of this design is that it dramatically reduces the number of treatments that are necessary, relative to a full factorial design, while still enabling researchers to evaluate the aspects of IGEs in groups that cannot be revealed by studies of dyadic IGEs: the potential effects of the genetic composition of the group on dyadic interactions among individuals [23][24][25][26]. Researchers studying eavesdropping [34] and audience effects [35] have used similar designs, demonstrating that the social context can influence dyadic behavioural interactions.…”
Section: Introductionmentioning
confidence: 99%
“…As we show here, however, male harassment can also disrupt female social behaviour (Wearmouth et al. ) and social networks, resulting in increased aggression among females, which likely has longer‐term fitness costs (Darden & Watts ). A substantial change in shoaling behaviour, for example, may have significant implications in the presence of predators.…”
Section: Discussionmentioning
confidence: 59%
“…Several authors observed that harassment encouraged shoaling with other females to dilute male sexual attention, thereby providing more time for feeding (Pilastro et al 2003;Dadda et al 2005;Agrillo et al 2006;Darden & Watts 2012). As we show here, however, male harassment can also disrupt female social behaviour (Wearmouth et al 2012) and social networks, resulting in increased aggression among females, which likely has longer-term fitness costs (Darden & Watts 2012). A substantial change in shoaling behaviour, for example, may have significant implications in the presence of predators.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation